2018
DOI: 10.1097/icl.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Level of Compliance in Orthokeratology

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 31 publications
6
31
0
Order By: Relevance
“…However, it has been reported that compliance with care procedures did not actually improve as the wearers grew older. 29 Good compliance is important to ensure safe lens wear, and has been shown to be associated with a reduced rate of contamination of contact lenses and accessories. 30,31 Serious complications, such as microbial keratitis, can lead to vision loss or blindness.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that compliance with care procedures did not actually improve as the wearers grew older. 29 Good compliance is important to ensure safe lens wear, and has been shown to be associated with a reduced rate of contamination of contact lenses and accessories. 30,31 Serious complications, such as microbial keratitis, can lead to vision loss or blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Non-compliance related to hygiene procedures and care procedures remains a serious concern and is a major causative factor of serious ocular complications for all contact lens modalities [156][157][158][159]. Over time, contact lens patients may become lax in lens care and handling techniques [160], and in adhering to the recommended aftercare schedule [161]. In China, poor lens care and inadequate hand washing were the two most common non-compliant behaviours in ortho-k lens wearers [161].…”
Section: Non-compliancementioning
confidence: 99%
“…Over time, contact lens patients may become lax in lens care and handling techniques [160], and in adhering to the recommended aftercare schedule [161]. In China, poor lens care and inadequate hand washing were the two most common non-compliant behaviours in ortho-k lens wearers [161]. The lens case has also been identified as the most contaminated item in new ortho-k lens wearers [162].…”
Section: Non-compliancementioning
confidence: 99%
“…Correct completion of compliance records is compulsory for individualization of health education to achieve care goals. Previous research has also found that non-compliance behaviors vary with different wearing times [ 15 , 28 ]. In addition, the OK lens wearing process is the most frequently asked question by parents in the Facebook community.…”
Section: Discussionmentioning
confidence: 99%
“…Regular monitoring of OK lenses during follow-up visits could aid in monitoring the growth of the axial length as well as reducing the risk of infection [ 14 ]. However, the risk of non-compliance among young children in wearing OK lenses is considerably higher than that of other age groups [ 15 ], which can affect the achievement of visual acuity among children [ 16 ]. Furthermore, non-compliance with the lens wear schedule may have a detrimental effect on the control of myopia progression.…”
Section: Introductionmentioning
confidence: 99%